Patrol Ship Management Efficiency Through Integrated Information System At The Class Ii Bitung Sea and Coast Guard Base - Kusuma, Joanda Arya; Masengi, Evi E.; Mamonto, Fitri H. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
To find out, identify and analyze the efficiency of operational data management of patrol vessels through an integrated information system at the Bitung Class II Coast Guard Base.In accordance with the problems that the researcher explains, the type of research used by the researcher is descriptive with a qualitative approach. The purpose of this research is to observe and find out what is to be researched..Based on the discussion above, it can be concluded that the efficiency of operational data management of patrol boats at PPLP Class II Bitung is not optimal, this is greatly influenced by the harmonious integration between procedures, resources, and information systems, namely: Procedures, although there are standard operational guidelines as reflected in the implementation of SIM KPLP, these procedures do not fully support real-time reporting and data processing. The technical reporting process of the ship is only carried out once a month, while other workflows such as logistics and administration still use a manual approach. This causes delays in decision making and lack of integration between units which has the potential to hinder the effectiveness and efficiency of patrol boat operations.